IMC1b Is a Putative Membrane Skeleton Protein Involved in Cell Shape, Mechanical Strength, Motility, and Infectivity of Malaria Ookinetes - Tremp, Annie Z. (American Society for Biochemistry and Molecular Biology, 2008)
Membrane skeletons are cytoskeletal elements that have important roles in cell development, shape, and structural integrity. Malaria parasites encode a conserved family of putative membrane skeleton proteins related to articulins. One member, IMC1a, is expressed in sporozoites and localizes to the pellicle, a unique membrane complex believed to form a scaffold onto which the ligands and glideosome are arranged to mediate parasite motility and invasion. IMC1b is a closely related structural paralogue of IMC1a, fostering speculation that it could be functionally homologous but in a different invasive life stage. Here we have generated genetically modified parasites that express IMC1b tagged with green fluorescent protein, and we show that it is targeted exclusively to the pellicle of ookinetes. We also show that IMC1b-deficient ookinetes display abnormal cell shape, reduced gliding motility, decreased mechanical strength, and reduced infectivity. These findings are consistent with a membrane skeletal role of IMC1b and provide strong experimental support for the view that membrane skeletons form an integral part of the pellicle of apicomplexan zoites and function to provide rigidity to the pellicular membrane complex. The similarities observed between the loss-of-function phenotypes of IMC1a and IMC1b show that membrane skeletons of ookinetes and sporozoites function in an overall similar way. However, the fact that ookinetes and sporozoites do not use the same IMC1 protein implies that different mechanical properties are required of their respective membrane skeletons, likely reflecting the distinct environments in which these life stages must operate.